2015
DOI: 10.1021/acs.inorgchem.5b01495
|View full text |Cite
|
Sign up to set email alerts
|

DFT Dissection of the Reduction Step in H2 Catalytic Production by [FeFe]-Hydrogenase-Inspired Models: Can the Bridging Hydride Become More Reactive Than the Terminal Isomer?

Abstract: Density functional theory has been used to study diiron dithiolates [HFe2(xdt)(PR3)n(CO)5-nX] (n = 0, 2, 4; R = H, Me, Et; X = CH3S(-), PMe3, NHC = 1,3-dimethylimidazol-2-ylidene; xdt = adt, pdt; adt = azadithiolate; pdt = propanedithiolate). These species are related to the [FeFe]-hydrogenases catalyzing the 2H(+) + 2e(-) ↔ H2 reaction. Our study is focused on the reduction step following protonation of the Fe2(SR)2 core. Fe(H)s detected in solution are terminal (t-H) and bridging (μ-H) hydrides. Although uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 56 publications
6
50
0
2
Order By: Relevance
“…It is often observed that CO ligands preferentially occupy sites trans to hydride ligands in diferrous complexes of the type [(μ-H)Fe 2 (SR) 2 (CO) 6− x (PR 3 ) x ] +. [21] The N–H positions were refined crystallographically, revealing the presence of both amido and amino ligands. Thus, [H 1 H] 0 is described as HFe 2 (pdt)(CO) 2 (κ 2 -PNH 2 )(κ 2 -PNH).…”
Section: Resultsmentioning
confidence: 99%
“…It is often observed that CO ligands preferentially occupy sites trans to hydride ligands in diferrous complexes of the type [(μ-H)Fe 2 (SR) 2 (CO) 6− x (PR 3 ) x ] +. [21] The N–H positions were refined crystallographically, revealing the presence of both amido and amino ligands. Thus, [H 1 H] 0 is described as HFe 2 (pdt)(CO) 2 (κ 2 -PNH 2 )(κ 2 -PNH).…”
Section: Resultsmentioning
confidence: 99%
“…DFT calculations have been performed with the pure functional BP86 and an all‐electron triple‐ζ basis set with polarization on all atoms (TZVP), as implemented in the TURBOMOLE 7.1.1 suite . This level of theory has provided good and consistent results in the reproduction of structural and reactivity features in bioinspired compounds and also very recently in other diiron catalysts for hydrogen evolution . In addition, the BP86/TZVP scheme was previously used to study the oxidative behavior of complex 1 in the absence and in the presence of CO .…”
Section: Methodsmentioning
confidence: 99%
“…These situations arise when bulky ligands are present, with reduction of the μ -H complex alleviating strain by allowing the metals to distance themselves from one another. 186 …”
Section: [Fefe]-h2asesmentioning
confidence: 99%